The Effect of Price and Service Quality on Consumer Satisfaction on Harapan Jaya Automotive and Car Wash District Tana Toraja - Chrismesi Pagiu; Yohanis Lotong Ta'dung (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This research aims to determine how big the influence of price and service quality on the level of satisfaction felt by consumers who use the services of Harapan Jaya Automotive And Car Wash Tana Toraja. The type of research used is descriptive quantitative research, namely the process of collecting data through questionnaires. For data collection methods using field research and library research, while for data collection procedures using a questionnaire (with a Likert scale), observation, interviews, and documentation. In determining the sample using the Slovin formula with a population average of 800 people and obtained a sample of 89 people.coefficientof and.correlationconsumer satisfaction (Y).